Intranasal immunization with inactivated chlamydial elementary bodies formulated in VCG-chitosan nanoparticles induces robust immunity against intranasal Chlamydia psittaci challenge - Zonghui Zuo (Nature Portfolio, 2021)
Abstract Vaccines based on live attenuated Chlamydia elementary bodies (EBs) can cause disease in vaccinated animals and the comparably safer inactivated whole EBs are only marginally protective. Recent studies show that a vaccine formulation comprising UV-inactivated EBs (EB) and appropriate mucosal delivery systems and/or adjuvants induced significant protective immunity. We tested the hypothesis that intranasal delivery of UV-inactivated C. psittaci EB formulated in Vibrio cholerae ghosts (VCG)-chitosan nanoparticles will induce protective immunity against intranasal challenge in SPF chickens. We first compared the impact of VCG and CpG adjuvants on protective immunity following IN mucosal and IM systemic delivery of EB formulated in chitosan hydrogel/microspheres. Immunologic analysis revealed that IN immunization in the presence of VCG induced higher levels of IFN-γ response than IM delivery or the CpG adjuvanted groups. Also, vaccine efficacy evaluation showed enhanced pharyngeal bacterial clearance and protection against lung lesions with the VCG adjuvanted vaccine formulation, thereby establishing the superior adjuvanticity of VCG over CpG. We next evaluated the impact of different concentrations of VCG on protective immunity following IN mucosal immunization. Interestingly, the adjuvanticity of VCG was concentration-dependent, since protective immunity induced following IN mucosal immunization showed dose-dependent immune responses and protection. These studies reveal that formulation of inactivated chlamydial antigens with adjuvants, such as VCG and chitosan increases their ability to induce protective immune responses against challenge.